Jurnal Kata: co-constructing an EFL student teachers personal experience of teaching practice - Joseph ernest mambu (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
the study inquires into how a student teachers pedagogical narrative is co constructed with a teacher educator